HUBUNGAN USIA DAN TINGKAT PENDIDIKAN DENGAN KESEHATAN MENTAL PADA IBU HAMIL DI PUSKESMAS KASIHAN I BANTUL YOGYAKARTA - Asmiwatty Zahra Uar,; Dwi Ernawati,; Sri Ratnaningsih, (Journal of Innovation Research and Knowledge, 2025)
Pregnancy is a natural process that requires efforts to prepare the mental health of pregnant women, as it impacts their perception of well-being and quality of life. Maintaining mental health is essential at all stages of life. Pregnant women with mental health disorders may experience depression or stress, and in severe cases, this can contribute to maternal and infant mortality. The World Health Organization (WHO) reports that approximately 10% of pregnant women worldwide suffer from depression. Objective: This study aims to determine the relationship between age and education level with mental health among pregnant women at Kasihan I Public Health Center in Bantul, Yogyakarta. Method: This research used a quantitative design with a cross-sectional approach. The sampling technique used was total sampling, resulting in a total of 71 respondents. Data were collected through interviews using the SRQ-20 questionnaire. Results: The results of the Chi-Square statistical test showed no significant relationship between age and education level with mental health among pregnant women, as the P-Values > 0.05, age (0.142) and education level (0.624). Conclusion: There is no relationship between age and education level with the mental health of pregnant women at Kasihan I Public Health Center in Bantul, Yogyakarta